Comparative study on seismic behavior of corroded RC columns strengthened by ECC combined with steel cage /fiber grid/CFRP - Che, Jialing; Liu, Chen; Wu, Ping; Li, Xinping; Liu, Haifeng; Doh, Shu Ing (Elsevier Ltd, 2024)
A method for strengthening was proposed to improve the seismic behavior of corroded reinforced concrete (RC) columns by using engineered cementitious composite (ECC) combined with a steel cage/fiber grid/carbon fibre reinforced plastics(CFRP). The corroded RC columns strengthened with ECC combined with a steel cage, fiber grid, and CFRP were subjected to low cyclic compression tests at design axial pressure ratios (n) of 0.3 and compared with corroded and uncorroded columns. Experimental results showed that ECC strengthening of corroded RC columns not only significantly improved their load-carrying capacity, displacement ductility, and energy dissipation capacity but also effectively reduced the degree of damage and stiffness degradation. The ductility coefficients of ECC/steel cage composite strengthened columns and ECC/CFRP composite strengthened columns are 35.58 % and 34.13 % higher, respectively, compared to ECC fully strengthened columns, while the ductility coefficient of ECC/fiber grid composite strengthened columns decreased by 4.33 % compared to ECC fully strengthened columns. Among them, the ECC/steel cage composite-strengthened columns exhibited the highest number of hysteresis loops, the strongest energy dissipation capacity, and the best strengthening effect. Additionally, a restoring force model for ECC-strengthened corroded RC columns was established, and its validity was verified through theoretical calculations.